Ways of sensing understanding the senses in society - Howes, David 1957-; Classen, Constance 1957- (Routledge, 2014)
"Ways of Sensing is a stimulating exploration of the cultural, historical and political dimensions of the world of the senses. The book spans a wide range of settings and makes comparisons between different cultures and epochs, revealing the power and diversity of sensory expressions across time and space. The chapters reflect on topics such as the tactile appeal of medieval art, the healing power of Navajo sand paintings, the aesthetic blight of the modern hospital, the role of the senses in the courtroom, and the branding of sensations in the marketplace. Howes and Classen consider how political issues such as nationalism, gender equality and the treatment of minority groups are shaped by sensory practices and metaphors. They also reveal how the phenomenon of synaesthesia, or mingling of the senses, can be seen as not simply a neurological condition but a vital cultural mode of creating social and cosmic interconnections. Written by leading scholars in the field, Ways of Sensing provides readers with a valuable and engaging introduction to the life of the senses in society"..